Effects of perfluoro modified sol-gel additive on UV-curable phosphorus containing urethane acrylate coatings - KARATAŞ, SEVİM (WILEY, 2018)
A series of UV-curable urethane acrylate (UA) hybrid oligomers containing bis[4-(ss-hydroxy propoxy) phenyl] phenyl phosphine oxide (BHPPPO) monomer were successfully synthesized via sol-gel method. Triethoxysilane modified perfluoropentane diol (Si-PFN) which is a novel organo alkoxysilane compound was successfully synthesized for the sol-gel reaction. When the contents of BHPPPO and the sol-gel precursor increased in the urethane coating formulations, it was determined that the gloss increased from 93 degrees to 146 degrees, the water absorption decreased from 27.2 to 7.9 wt% and the tensile strength increased 95.1MPa from 222.4 MPa. The results of the thermal gravimetric analysis showed that with the addition of BHPPPO and the sol-gel solution into the UAs the weight losses were shifted to higher temperatures and resulted in increasing the char ruins of them. The limiting oxygen index values of them slightly changed compared to the neat UA. For deionized water/ethylene glycol the contact angle values of the hybrids ranged from 63 degrees/61 degrees to 87 degrees/75 degrees. These results indicate that the hybrid coating films have a hydrophobic surface. Scanning electron microscope studies indicated that between the inorganic and organic phases chemical interaction was reasonable. The scanning electron microscopy-energy dispersive spectrometry results confirmed the P, Si, and F intensification on the surface of the hybrid coating. These results suggest that the hybrids containing phosphorus have provided a potential application as the coating materials in industry. J. VINYL ADDIT. TECHNOL., 24:E133-E145, 2018. (c) 2018 Society of Plastics Engineers
Keywords: POLYURETHANE ACRYLATES; COLLOIDAL SILICA; NANOCOMPOSITES; POLYIMIDES; POLYMERS; ADHESIVE; KINETICS; BEHAVIOR; POLYOL; RESIN